2016
DOI: 10.1016/j.neuroimage.2015.11.020
|View full text |Cite
|
Sign up to set email alerts
|

Causal evidence that intrinsic beta-frequency is relevant for enhanced signal propagation in the motor system as shown through rhythmic TMS

Abstract: Correlative evidence provides support for the idea that brain oscillations underpin neural computations. Recent work using rhythmic stimulation techniques in humans provide causal evidence but the interactions of these external signals with intrinsic rhythmicity remain unclear. Here, we show that sensorimotor cortex follows externally applied rhythmic TMS (rTMS) stimulation in the beta-band but that the elicited responses are strongest at the intrinsic individual beta peak frequency. While these entrainment ef… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
92
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 80 publications
(101 citation statements)
references
References 60 publications
7
92
0
2
Order By: Relevance
“…Importantly, some studies have shown that the up-regulation of brain oscillations at target frequencies is more effective when the frequency of stimulation matches the natural rhythms, than when offset (see e.g. [32] for results in the human brain), which is in line with models of entrainment [42].…”
Section: Rhythmic Ntbs Interventions (And the Role Of Stimulation Frementioning
confidence: 64%
See 1 more Smart Citation
“…Importantly, some studies have shown that the up-regulation of brain oscillations at target frequencies is more effective when the frequency of stimulation matches the natural rhythms, than when offset (see e.g. [32] for results in the human brain), which is in line with models of entrainment [42].…”
Section: Rhythmic Ntbs Interventions (And the Role Of Stimulation Frementioning
confidence: 64%
“…In terms of electrophysiology, several studies have shown an up-regulation of oscillatory activity at the target frequency, this is the case both for interventions with frequency-tuned rTMS ( [31][32][33]) and tACS (for EEG see [34]; for MEG see ( [35][36][37], see also [38] for tDCS), despite the mechanisms of interaction between a particular stimulation type and the underlying neurons most likely being fundamentally different. Specifically, while frequency-tuned TMS will likely entrain oscillatory activity by phase-resetting ongoing oscillations through its depolarizing action [39,40], tACS/o-TDCS will affect brain oscillations by its modulatory influences at the level of membrane potentials (e.g.…”
Section: Rhythmic Ntbs Interventions (And the Role Of Stimulation Frementioning
confidence: 99%
“…They observed that the stimulation is able to produce, and progressively enhance, parietal alpha activity, and that this effect is dependent on the phase of ongoing alpha oscillations prior to the stimulation. Similarly, studies have shown that rTMS can entrain beta oscillations in non-visual areas such as prefrontal cortex (Hanslmayr et al, 2014) and motor cortex (Romei et al, 2015). These results confirm that rTMS is able to entrain ongoing neural oscillations, consequently impacting brain functions and subsequent perceptual performance (Romei et al, 2016 for a comprehensive review).…”
Section: Rhythmic Non-invasive Brain Stimulationmentioning
confidence: 93%
“…Mally y Dinya [27]. Este tipo de estimulación es efectiva en el punto en que la derivada del campo eléctrico inducido es máxima [26].…”
Section: Clasificadorunclassified
“…Un estudio realizado por Romei et al [27] utiliza esta técnica a diferentes frecuencias. c) tCS: Existen diferentes tipos de estimulación por corriente.…”
Section: Clasificadorunclassified